2019
DOI: 10.1016/j.eclinm.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation Availability and Density around the Globe

Abstract: BackgroundDespite the epidemic of cardiovascular disease and the benefits of cardiac rehabilitation (CR), availability is known to be insufficient, although this is not quantified. This study ascertained CR availability, volumes and its drivers, and density.MethodsA survey was administered to CR programs globally. Cardiac associations and local champions facilitated program identification. Factors associated with volumes were assessed using generalized linear mixed models, and compared by World Health Organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
192
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 167 publications
(199 citation statements)
references
References 25 publications
(34 reference statements)
1
192
0
6
Order By: Relevance
“…54 Similarly, global access to cardiac rehabilitation is poor, with cardiac rehabilitation only available in approximately half of the countries, globally. 55 Methods of funding included public, private and hybrid funding, all varying by country, with financial constraints the greatest barrier to cardiac rehabilitation, globally. 55 Lack of funding for PH programs, particularly in the outpatient setting, was noted in the present study and by Keen et al 50 This reflects the current funding climate in Australia and overseas, 40 where a large proportion of health resources are directed towards the acute care (inpatient) setting.…”
Section: Barriers To Exercisementioning
confidence: 99%
“…54 Similarly, global access to cardiac rehabilitation is poor, with cardiac rehabilitation only available in approximately half of the countries, globally. 55 Methods of funding included public, private and hybrid funding, all varying by country, with financial constraints the greatest barrier to cardiac rehabilitation, globally. 55 Lack of funding for PH programs, particularly in the outpatient setting, was noted in the present study and by Keen et al 50 This reflects the current funding climate in Australia and overseas, 40 where a large proportion of health resources are directed towards the acute care (inpatient) setting.…”
Section: Barriers To Exercisementioning
confidence: 99%
“…ICCPR, a member of the World Heart Federation, facilitated program identification for this audit. This was a cross-sectional study, details of which have been reported elsewhere [19,20]. In this report, we summarize CR availability and provision in India specifically.…”
Section: Methodsmentioning
confidence: 94%
“…Almost half of countries in the world do not have CR. Despite the availability of CR in India (given the high burden of CVD), the unmet need for CR is highest in India of any country in the world [19,20,23]. The programs that are available were clustered in the southern states of India, leaving major gaps in services in the North, East and West.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations